Timing of SGLT2i initiation after acute myocardial infarction - Dirk von Lewinski; Ewald Kolesnik; Faisal Aziz; Martin Benedikt; Norbert J. Tripolt; Markus Wallner; Peter N. Pferschy; Friederike von Lewinski; Nora Schwegel; Rury R. Holman; Abderrahim Oulhaj; Deddo Moertl; et al. (Cardiovascular Diabetology, 2023)
Abstract Background Pharmacological post-MI treatment is routinely initiated at intensive/cardiac care units. However, solid evidence for an early start of these therapies is only available for dual platelet therapy and statins, whereas data on beta blockers and RAAS inhibitors are heterogenous and mainly limited to STEMI and heart failure patients. Recently, the EMMY trial provided the first evidence on the beneficial effects of SGLT2 inhibitors (SGLT2i) when initiated early after PCI. In patients with type 2 diabetes mellitus, SGLT2i are considered “sick days drugs” and it, therefore, remains unclear if very early SGLT2i initiation following MI is as safe and effective as delayed initiation. Methods and results The EMMY trial evaluated the effect of empagliflozin on NT-proBNP and functional and structural measurements. Within the Empagliflozin group, 22 (9.5%) received early treatment (< 24 h after PCI), 98 (42.2%) within a 24 to < 48 h window (intermediate), and 111 (48.1%) between 48 and 72 h (late). NT-proBNP levels declined by 63.5% (95%CI: − 69.1; − 48.1) in the early group compared to 61.0% (− 76.0; − 41.4) in the intermediate and 61.9% (− 70.8; − 45.7) in the late group (n.s.) within the Empagliflozin group with no significant treatment groups—initiation time interaction (pint = 0.96). Secondary endpoints of left ventricular function (LV-EF, e/e`) as well as structure (LVESD and LVEDD) were also comparable between the groups. No significant difference in severe adverse event rate between the initiation time groups was detected. Conclusion Very early administration of SGLT2i after acute myocardial infarction does not show disadvantageous signals with respect to safety and appears to be as effective in reducing NT-proBNP as well as improving structural and functional LV markers as initiation after 2–3 days.